Tailoring the crystallite size of Co3O4/SiO2 catalyst using organic-metal matrix method - Zhao, Y; Qin, X; Yao, B; Gonzalez-Cortes, S; Xiao, T (Elsevier, 2018)
In this work, a series of SiO2 supported Co catalysts have been prepared by adding urea or ruthenium to the cobalt precursor solution compared with the catalysts prepared without using urea. The characterization results show that cobalt is present as Co3O4 over the silica supports. The addition of urea to the catalyst precursor helps to generate smaller crystallite even at very high cobalt loading, while impregnation without using urea results in larger crystallite size as Co loading increases. Likewise, the addition of Ru to the catalyst precursor leads to a more uniform crystallite of Co3O4, and can help to lower the Co3O4 crystallite size to some extent, which has the similar effect on the catalyst prepared with urea. We have also shown that the support pore size and volume do have significant effect on the crystallite size of the cobalt oxide. The catalytic performances of the Co/SiO2 catalysts prepared with and without adding urea have been evaluated for Fischer Tropsch synthesis and the catalyst prepared using urea demonstrates significantly improved catalyst activity as well as selectivity to C5+.